The Photography and Memory Project: Adapting an Intergenerational Program During a Global Pandemic. (17th December 2021) - MacInnes, Roddy; Walker, Anne; DelPo, Amy; Hasche, Leslie; Steward, Andrew; Schilz, Matthew; de Fries, Carson
Abstract: Since 2019, a university-community partnership has connected undergraduate students with older adults from independent living and community-based settings (i.e., library, art museum) for a photography-based intergenerational program. This study compares the implementation and impacts of this photography-based intergenerational program both in an in-person format before the COVID-19 pandemic (n=34) and an online format during the COVID-19 pandemic (n=25). Pre- and post- results from older adult and undergraduate student participants regarding social connection and evaluation comments from program participants and staff were compared between the pre-pandemic, in-person format, and the same program's offering the next year in a virtual format. Results indicate that the benefits of this intergenerational photography program were experienced at a similar level during and before COVID-19. Findings demonstrate that intergenerational programs could effectively continue in remote formats, while also identifying potential challenges in implementation for staff regarding managing logistics and maintaining engagement among participants.